Leadership Management of Community Learning Center (Pkbm) Institutions In Enhancing Tutor Performance At Pkbm Bina Muda, Muara Telang District - Indra Putra Jaya; Mahasir; Nuril Furkan (Graduate Program Magister Manajemen Pendidikan, 2026)
This study aims to analyze the leadership management practices of the Community Learning Center (PKBM) in enhancing the performance of equivalency education tutors at PKBM Bina Muda, Muara Telang District. This study employed a descriptive qualitative approach involving six informants consisting of the Head of PKBM, one supervisor, two tutors, and two learners. Data were collected through observation, in-depth interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing. The findings indicate that leadership management is implemented through systematic planning, task organization, effective communication, continuous supervision, and regular learning evaluation. These leadership practices improve tutors’ discipline, professional responsibility, work motivation, and instructional performance. Supporting factors include effective communication, collaboration, tutor commitment, and managerial support, whereas limited facilities, tutors’ multiple responsibilities, and diverse learner characteristics remain major challenges. This study contributes to educational management by providing a contextual model of leadership management for strengthening tutor performance in non-formal education institutions.